Sacred cows and chicken Manchurian : the everyday politics of eating meat in India - Staples, James, 1966- (Culture, place, and nature., 2020)
"Observance of what people in present-day India eat and do not eat, the styles and contexts within which they do so, and the disparities between rhetoric and everyday action prompt vital questions concerning what it is to be Indian in the early twenty-first century. The current "beef situation" exposes, like no other issue, the central fault lines that run across contemporary Indian society. Sacred Cows and Chicken Manchurian explores contemporary cattle slaughter and beef-eating in India and considers what has led to the apparent turn away from the hitherto secularist approach of post-independence India. The book draws on ethnographic research in both rural and urban South India with domestic cattle owners, brokers, butchers, and meat eaters. It brings nuance to existing accounts by journalists, historians, and others by charting how ordinary people navigate the current febrile political climate in their everyday lives. In doing so, it avoids an overly simplistic binary opposition between those who oppose the slaughter of cattle and those who view beef consumption as a fundamental right. Locating debates and actions concerning beef eating in relation to caste and community, the book offers a fine-grained exploration of the current situation as it is experienced on the ground, comprehensively locating it within the wider anthropology of food and eating in the region"--